Controlling donor crystallinity and phase separation in bulk heterojunction solar cells by the introduction of orthogonal solvent additives. (8th May 2018) - Alam, Shahidul; Meitzner, Rico; Kaestner, Christian; Ulbricht, Christoph; Hoeppener, Stephanie; Egbe, Daniel A.M.; Schubert, Ulrich S.; Hoppe, Harald
ABSTRACT: The bulk heterojunction morphology of organic solar cells widely controls their device efficiency and stability. Structural order and domain size of the donor phase strongly impact the charge separation efficiency, recombination rates, and the hole percolation through the bulk to the electrode. Herewith, we report a comprehensive study on the control of polymeric order already initiated in solution by the introduction of orthogonal solvent additives to the common solution of anthracene containing poly(p-phenylene-ethynylene)-alt-poly(p-phenylene-vinylene) (PPE-PPV) copolymer, bearing statistically substituted linear octyloxy and 2-ethylhexyloxy side-chains in 1:1 ratio along the backbone (AnE-PVstat), and fullerene derivative phenyl-C61-butyric acid methyl ester (PCBM). The first solvent, a 1:1 blend of chlorobenzene and chloroform, had been discovered to promote phase separation in solution and deposited films. This effect could be further enhanced and was precisely controlled by addition of methanol to the common solution in various volume fractions. Thus the ability to transfer the polymer aggregates from the solution into films was applied to solar cells and is investigated in detail.